Detection of Adenovirus antigen and its correlation with clinical signs among children with gastroenteritis - B.Mahmood, Dhuha; Al-suhail, Raghad.; G.Al-Hamdani, Faisal; A.Salih, Rafah (Iraqi Journal of Science, 2023)
A total of 90 stool sample was collected from patients with gastroenteritis todetect adenovirus antigen among diarrhea cases. They were tested by general stoolexamination (GSE), rapid immunochromatographic test and Enzyme LinkedImmunosorbent Assay (ELISA). GSE showed that adenovirus gastroenteritisinfection resulted in non-bloody diarrhea, the existence of RBCs in 7% and Pus in37% of the samples, Entamoeba histolytica trophozoite and cyst were seen in 3%and 2% of the samples respectively. The rapid test showed that 21% of sampleswere positive for rotavirus, 8% for adenovirus and 3% for astrovirus. Meanwhile,the ELISA test showed that adenovirus was positive in 9% of the samples. Thesefindings established the evidence that adenovirus is significantly the second viralagent that cause gastroenteritis among children after rotavirus. Furthermore, it mustbe stated that rapid diagnostic methods are important for detection of adenovirusinfection.